Malaysia’s Knowledge Economy: The Practice of Collaborative Pedagogy to Realize National Goals - Campbell, James (INTI International University, 2007)
The nature of pedagogy and the collaboration between international parties in subject design ameliorates some of the more negative characteristics of globalized education. I argue that the nature of globalization is to be found in the small and ongoing practices that constitute collaboration between differing parties. In this way, what globalization means is in fact constantly a negotiated contingent and is never settled. My argument is that reductive critiques of internationalization are far too simplistic. The example of EME 150 and the uptake through the Malaysian educational system of some of its components is an example not of ‘imposition’ or ‘imperialism’ but rather of a more negotiated and collaborative pedagogy that points to some of the benefits of cooperation, collaboration and by inference of globalization.